Monthly variation in the lipid composition and content of Pacific oysters, \(Crassostrea gigas\), cultured in Van Don, Quang Ninh - LeThi , Thanh Tra; Pham Quoc , Long; Ngo Quang , Dai; Lai Phuong, Thao; Le Hong, Nhung; Dang Thi , Phuong Ly; Hoang Thi, Bich; Tran Quoc, Toan (Vietnam Journal of Marine Science and Technology, 2023)
We conduct a study to investigate the year-round fluctuation of lipid composition and content in Pacific oysters (Crassostrea gigas) cultured in Van Don, Quang Ninh, for the first time. Our results showed that the total lipid content of oysters ranged from 1% to 1.6%, with the highest levels observed during their pre-reproductive period (July and December). Polyunsaturated fatty acids were the most abundant type of lipids in oysters, ranging from 41.66% to 53.36%. We identified six lipid classes in Pacific oysters, with the three dominant classes being PoL, ST, and TG, which exhibited significant variation, with the highest variability observed in May and June and the lowest in July. The primary fatty acids in oyster lipids were 14:0, 16:0, 18:0, 18:1n-7, 20:4n-6, 20:5n-3, and 22:6n-3. In summary, our study provides novel insights into the lipid composition and content of Pacific oysters cultured in Van Don, Quang Ninh.The results demonstrate the temporal variability in lipid classes and fatty acid composition throughout the year, with the highest lipid content observed during the pre-reproductive period. These findings could contribute to better understanding the nutritional value of Pacific oysters and inform future aquaculture practices.